Spór o Wilno: wielość obrazów - Chutnik, Agata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
Vilnius plays an important role both for Lithuanian Poles and Lithuanians. By Lithuanians, it is understood as the historical capital of the state, the beginnings of the Lithuanian state. For Lithuanian Poles, in turn, Vilnius it is often a place of identification and a private homeland, a place of residence their ancestors. This article relates to the images of Vilnius presented by narrators during the interviews. I will try to illustrate the multiplicity of approaches using quotes from narrators. These images will show how important history is, especially in contemporary public debate and interpersonal relations, despite frequent declarations that it is currently not playing a role in everyday life.